E-learning Media Development “Recycle” - Pahuyut, Phuridech; Shuprutnawong , Phiphatphon; Phituksuksunti, Piya; Kotdee, Aniwat; Ritporn , Jakpong; Khewkeaw, Arunee (Interdisciplinary Academic and Research Journal, 2023)
At present, the problem of solid waste is a problem that all parties concerned have given importance to and must work together to solve to the best of their ability. Teaching and learning using technology to stimulate memory and increase learning skills requires a variety of media to attract learners to focus on what they are interested in. Learning and self-improvement effectively. The purposes of this research were 1) to study on students’ proficiency performance in recycling with 80/80 criteria determination and 2) to compare the proficiency study with Pre-test and Post-test with the supplementary in recycling for primary school class level 2. The target group was 27 Primary school grades 2 in semester 1, the academic year of 2565 at Watsaladang school, Bangkok which was randomized by purposive sampling. The instruments were sets of supplementary recycling, the achievement test, and the satisfaction test. The statistical procedures employed to examine the data were Percentage, Mean, Standard Deviation, t-test Dependent. The results of the study were the following; (1) The supplementary in recycle for primary school class level 2 at Watsaladang indicated a proficiency score of E1/E2 at 92.69/89.42 above the criteria determination of 80/80. And (2) Students’ proficiency performance in recycling for primary school class level 2 at Watsaladang school, Bangkok indicated a higher score after learning a statistically significant difference at level .01